Early Land Plants Today: Index of Liverworts & Hornworts 2009–2010 - Söderström, Lars; Hagborg, Anders; Crosby, Marshall R.; Konrat, Matt Von (Phytotaxa, 2012)
A widely accessible list of known plant species is a fundamental requirement for plant conservation and has vast applications. An index of published names of liverworts and hornworts between 2009 and 2010 is provided as part of a continued effort in working toward producing a world checklist of this group. Included in the list are also names overlooked by earlier indices. The list includes 30 higher taxa, 250 species, 52 infraspecific taxa, 31 autonyms, and two fossils for 2009 and 2010. A number of taxa not covered by the earlier indices for 2000-2008 are also included.